Role of defects on the magnetic behaviour of the geometrically frustrated spinel ZnFe 2 O 4 - Salcedo Rodriguez, Karen Lizeth (2018)
Defective zinc ferrites ZnFe$_2$O$_{4-δ}$ obtained by vacuum annealing bulk Zn-ferrite at different temperatures TAnn were investigated by using XANES at Zn-K, Fe-K and XMCD at Fe-L$_{2,3}$ edges, static and dynamic magnetic measurements. The cation inversion that confers to the starting ferrite a weak ferromagnetic response is progressively lost when TAnn surpasses 250 °C. Consequently, there is a detriment of the magnetic response that reaches its lower value for TAnn around 370 °C, being the latter coincident with a negligible non-equilibrium occupancy. Above TAnñ 450 °C the ferrite progressively enhances its magnetic response. In such case, even though Zn and Fe occupy non-equilibrium sites at surface regions, the deficiency of oxygen predominates over inversion and the former triggers an increment of the magnetic coupling between Fe$^{3+}$ at octahedral spinel sites. We discuss the magnetic results that account for spin-glass and/or cluster-glass behavior of this geometrically frustrated compound as due to the randomness and frustration introduced by local defects.